Assessing the impact of nutri-score labelling and product availability on consumer choice - Deirdre A. Robertson; Ylva Andersson; Pete Lunn (The Economic and Social Research Institute (ESRI), 2022)
Nutritional labelling is a means of communicating the nutritional content of food to consumers. When a nutritional label is salient and understandable, consumers tend to make more healthy choices. Nutritional labelling policies can also influence providers by incentivising manufacturers to reformulate recipes or to introduce healthier products to their range. While existing strands of research investigate the effect of nutritional labels on both consumer behaviour and provider behaviour, less is known about the relationship between the two. This study tested the effects of the nutritional label, Nutri-Score, and the availability of healthier options on real consumer decisions in an online purchasing task in Ireland. Consumers who saw Nutri-Score applied to snack products made healthier purchases, on average, than consumers who did not. Consumers who shopped in a market with more healthy options made healthier purchases than those who shopped in the current market. Our results are consistent with these two effects being additive. Hence, if the label is taken up widely, positive effects are possible via both changes to consumer choice and alterations to product ranges. Although effect sizes were relatively small, such modest dietary changes can generate meaningful effects across populations and over the lifespan.
Keywords: 330; Food choice; Nutritional Labels; Nutri-Score; Availability; Consumer Behaviour